ANALISIS KOMPETENSI SUPERVISOR PENDIDIKAN PADA LEMBAGA PENDIDIKAN ISLAM - Rusmini; Fauzi, Irfan Mohd; Yusuf, M. (Irfani, 2026)
Educational supervisors’ competence plays a strategic role in enhancing the quality of Islamic education. This study aims to examine the conceptual framework, roles, and strategies for strengthening supervisors’ competencies within the context of Islamic education. The research employs a library research design using a qualitative content analysis approach through the stages of decontextualization and recontextualization. The analytical process involves: (1) data reduction through the selection and summarization of key points from primary and secondary sources; (2) categorization based on thematic dimensions of supervisory competence; and (3) interpretation and conceptual synthesis to construct a coherent and systematic argument. The findings reveal that supervisory competence encompasses six principal dimensions: personal competence, managerial supervision, academic supervision, educational evaluation, research and development, and social competence integrated with Islamic values. These dimensions collectively contribute to strengthening teachers’ professionalism, enhancing institutional management effectiveness, and improving the quality of value-based learning in Islamic educational institutions. The study further emphasizes that strategies for developing supervisors’ competence should be systematically designed through continuous professional development programs, enhancement of research capacity and digital literacy, mentoring and value-based coaching grounded in Islamic principles, as well as performance evaluation based on measurable quality indicators. Therefore, the development of supervisory competence should not merely be regarded as regulatory compliance, but rather as a strategic investment in sustaining the quality and competitiveness of Islamic educational institutions